Landscape, memory and history : anthropological perspectives - Stewart, Pamela J.; Strathern, Andrew (London ; Sterling, Virginia : Pluto Press, 2003)
"How do people perceive the land around them, and how is that perception changed by history? This book explores this question from an anthropological angle, assessing the connections between place, space, identity, nationalism, history and memory in a variety of different settings around the world. Taking historical change and memory as key themes, it is a broad study that will appeal to a readership across the social sciences. Contributors from North America, Australia, New Zealand, Taiwan, and Europe explore a wide variety of case studies that includes seascapes in Jamaica; the Solomon Islands; the forests of Madagascar; Aboriginal and European notions of landscape in Australia; place and identity in 19th century maps and the bogs of Ireland; contemporary concerns over changing landscapes in Papua New Guinea; and representations of landscape and history in the poetry of the Scottish Borders."--
Introduction / Pamela J. Stewart and Andrew Strathern -- Iconic images: landscape and history in the local poetry of the Scottish borders / John Gray -- Céide Fields: natural histories of a buried landscape / Stuart McLean -- Landscape representation: place and identity in nineteenth-century ordnance survey maps of Ireland / Angèle Smith -- Memories of ancestry in the forests of Madagasacar / Janice Harper -- Moon shadows: aboriginal and European heroes in an Australian landscape / Veronica Strang -- History, mobility and land use interests of aborigines and farmers in the East Kimberly in North-West Australia / Ruth Lane -- Co-present landscapes: routes and rootedness as sources of identity in highlands New Guinea / Michael O'Hanlon and Linda Frankland -- 'Island builders': landscape and historicity among the Langalanga, Solomon Islands / Pei-yi Guo -- Biography, ecology, political economy: seascape and conflict in Jamaica / James G. Carrier.
Includes bibliographical references and index.
Pamela J. Stewart is Professor of Anthropology at the University of Pittsburgh, USA. Dr Andrew Strathern is Andrew Mellon Professor of Anthropology at the University of Pittsburgh, USA.
English.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Landscape assessment; Landscape changes; Landscapes -- Social aspects; Geographical perception; Paysages -- Évaluation.; Paysages -- Modifications; Paysages -- Aspect social; Perception géographique.; Miriwoong -- Miriuwung people (K29) (WA SD52-14); Gajerrong -- Gajirrawoong people (K37.1) (WA SD52-15); Koko Bera people (Y85) (Qld SD54-15); East Kimberley area (North NT SD52-15); East Kimberley area (WA SD52, SE52); Cape York Peninsula (Qld SC54, SD54, SD55); Trubanamen (Qld NW Cape York SD54-15); Native title -- Agreements -- Indigenous Land Use; Demography -- Population mobility; Economic sectors -- Agriculture and horticulture; Race relations -- Violent; Indigenous peoples -- Pacific; 73.99 ethnology: other; SOCIAL SCIENCE -- Human Geography; SOCIAL SCIENCE -- Anthropology -- Cultural; Geographical perception; Landscape assessment; Landscape changes; Landscapes -- Social aspects; Anthropologie; Landschaft; Ethnische Identität; Anthropogeografie; Landschappen; Antropologische aspecten; landschap; landscape; fysiografische elementen; physiographic features; perceptie; perception; verandering; change; antropologie; anthropology; geschiedenis; history; omgevingspsychologie; environmental psychology; Land Evaluation; Environmental Psychology; Landevaluatie; Omgevingspsychologie; Aufsatzsammlung